Tin tannates and iron tannates in corrosion-inhibiting coatings - Giúdice, Carlos A. (1998)
The efficiency of the coating systems in the protection of metallic substraía depends fundamentally, in relation with formulation variables, on the type and contení of corrosion-inhibitive pigment, the characteristics of the film forming material and the pigment / binder ratio in volume. Conceming the pigment, there is not doubt that the use of some inhibitors in anticorrosive paints is actually an important source generating toxicity problems both for the worker andfor the environment. This problem is extended to the applicator and álso to the removal operation of oíd coatings. In this research tin tcamates and iron tannates were employed as inhibitive pigments in anticorrosive paints. The mentioned metallic tannates were prepared on laboratory scale under controlled operative conditions, carrying out the reaction between the metallic ions and the polyphenolic groups of condensed tannins extracted from “quebracho ” heartwood (Schinopsis sp.).